2006
DOI: 10.1074/jbc.m513304200
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like Receptor-2 Is Essential for the Development of Palmitate-induced Insulin Resistance in Myotubes

Abstract: Fatty acids can activate proinflammatory pathways leading to the development of insulin resistance, but the mechanism is undiscovered. Toll like receptor 2 (TLR2) recognizes lipids, activates proinflammatory pathways, and is genetically associated with inflammatory diseases. This study aimed to examine the role of TLR2 in palmitate-induced insulin resistance in C2C12 myotubes. Treatment with palmitate rapidly induced the association of myeloid differentiation factor 88 (MyD88) with the TLR2 receptor, activated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
194
3
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 234 publications
(205 citation statements)
references
References 53 publications
6
194
3
2
Order By: Relevance
“…For example, palmitate induced IL-6 production and inflammatory signalling, leading to inhibition of insulin-activated signal transduction through TLR2 in myotubes [21]. In addition, inhibition of TLR2 expression by TLR2 antisense oligonucleotide improves insulin sensitivity and signalling in muscle and WAT from mice fed the HF diet [38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, palmitate induced IL-6 production and inflammatory signalling, leading to inhibition of insulin-activated signal transduction through TLR2 in myotubes [21]. In addition, inhibition of TLR2 expression by TLR2 antisense oligonucleotide improves insulin sensitivity and signalling in muscle and WAT from mice fed the HF diet [38].…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that the fatty acid composition plays a central role in ligand recognition and receptor activation for TLR2. Furthermore, other studies demonstrated that TLR2 is involved in NEFA-induced insulin resistance [21][22][23]. It is reasonable to postulate that the fatty acid moiety from nutrients could potentially activate TLR2 and transduce the inflammatory signals.…”
Section: Introductionmentioning
confidence: 99%
“…Intriguingly, both TLR2 (which heterodimers with TLR1, or TLR6) and TLR4 recognise lipid-based structures; classically bacterial lipopeptides and lipopolysaccharide, respectively. Recent studies have shown that NEFAs, including palmitate and oleate, can activate both TLR2 and TLR4 signalling to induce proinflammatory cytokine production in various tissues, leading to an impairment of tissue-specific effects [15][16][17][18][19]. In addition, both Tlr2 −/− and Tlr4 −/− mice show improvements in the metabolic syndrome associated with HFD-induced obesity [17,[20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, diacylglycerol, but not ceramide, is increased in L6 myotubes after a 6 h incubation with palmitate (data not shown). Furthermore, a role for TLR-2 has recently been implicated in lipidinduced insulin resistance in skeletal muscle [47].…”
mentioning
confidence: 99%